Perceived Relationship Between Organizational Citizenship Behavior and Human Resource Practices of General Department of Taxation in Cambodia: Implications for Staff Performance Interventions - Sopunna Sor; Sarom Mok; Somuny Som (Fakultas Keguruan dan Ilmu Pendidikan - Universitas Gresik, 2026)
Organizational citizenship behavior and human resource practices are critical determinants of employee performance in public sector institutions; however, limited research has examined their predictive influence within taxation agencies in developing countries. The purpose of this study was to determine whether staff performance at the General Department of Taxation (GDT) could be predicted by organizational citizenship behavior and human resource practices. A total of 123 GDT staff members participated in the study. The study employed a quantitative, non-experimental research design using a correlational approach and regression analysis. The statistical methods used included regression analysis, Pearson’s correlation coefficient (r), and mean analysis. The findings revealed that GDT staff performance, perceived human resource practices, and organizational citizenship behavior were all rated at a high level. The results demonstrated significant relationships between GDT staff performance and both human resource practices and organizational citizenship behavior. Specifically, GDT staff performance was significantly predicted by three dimensions of organizational citizenship behavior: (1) civic virtue, (2) conscientiousness, and (3) altruism. However, among the dimensions of human resource practices, only screening and selection significantly predicted GDT staff performance. Overall, the findings indicated that organizational citizenship behavior and human resource practices jointly contributed to the prediction of GDT staff performance. To enhance workplace culture, employee engagement, and organizational effectiveness, this study highlights the importance of integrating organizational citizenship behavior and human resource practices into a coherent strategic framework.